Mediation Role of Work Motivation: Organizational Commitment and Work Engagement on Employee Performance - Jufrizen Jufrizen; Bella Olivia Rizki; Muhammad Arif (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Sumatera Utara, 2022)
This study aims to analyze the effect of motivational commitment, motivational interaction, the effect of commitment on employee performance, the effect of work on employee performance, the effect of motivation on employee performance and the influence of organizational commitment on employee performance through motivation as an intervention variable at PT. Telekomunikasi Indonesia Tbk Witel Medan. In this study using associative research with a sample of 43 respondents who are permanent employees at PT. Telekomunikasi Indonesia Tbk Witel Medan. The data collection technique used in this study is a questionnaire, to analyze the data and information needed, the authors use path analysis techniques used for testing using Partial Least Square (Smart PLS). The results showed that organizational commitment had a significant positive effect on work motivation, work engagement had a positive but not significant effect on work motivation, commitment had a positive and significant effect on employee performance, work engagementhad a positive and significant effect on employees, work motivation had a significant positive effect on performance. employees, organizational commitment that has a positive and significant effect on employees through work motivation and work engagement which has a significant effect on employee performance through work motivation at PT. Telekomunikasi Indonesia Tbk Witel Medan.